Web-based Tailored Intervention for Preparation of Parents and Children for Outpatient Surgery (WebTIPS): Development - Kain, Zeev N. (Anesth Analg, 2015)
BACKGROUND: Due to cost-containment efforts, preparation programs for outpatient surgery are currently not available to the majority of children and parents. The recent dramatic growth in the Internet presents a unique opportunity to transform how children and their parents are prepared for surgery. In this article we describe the development of a Web-based tailored preparation program for children and parents undergoing surgery (WebTIPS). DEVELOPMENT OF PROGRAM: A multidisciplinary taskforce agreed that a Web-based tailored intervention comprised of intake, matrix and output modules was the preferred approach. Next, the content of the various intake variables, the matrix logic and the output content was developed. The output product has a parent component and a child component and is described in http://surgerywebtips.com/about.php. The child component makes use of preparation strategies such as information provision, modeling, play and coping skills training. The parent component of WebTIPS includes strategies such as information provision, coping skills training, relaxation and distraction techniques. A reputable animation and Web-design company developed a secured Web-based product based on the above description. CONCLUSIONS: In this article we describe the development of a Web-based tailored preoperative preparation program that can be accessed by children and parents multiple times before and after surgery. A follow-up article in this issue of Anesthesia & Analgesia describes formative evaluation and preliminary efficacy testing of this Web-based tailored preoperative preparation program.